Pengaruh Kualitas Produk, Persepsi Harga, Dan Citra Merek Terhadap Minat Beli Ulang Laptop Acer Di Kota Bandung - Muhammad Hanif Muhsinin; Esi Fitriani Komara (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research is motivated by the results of the Kurious survey from the Katadata Insight Center (KIC), Acer is the second most popular laptop in Indonesia, which is 79.2% of the total respondents. Based on the top brand award in 2022, Acer laptops are ranked first in the notebook or laptop category with a score of 27.1%. However, in 2023 there was a significant decrease in the Acer brand laptop, which was 5.90% compared to 2022. This indicates a decrease in repurchase interest in Acer brand laptops. This study aims to analyze the effect of product quality, price perception, and brand image on repurchase interest in Acer laptops in Bandung City. The d|at|a collection technique used is nonprob|ability s|ampling with convenience s|ampling rese|arch with |a tot|al of 120 respondents of |Acer l|aptop users who live in B|andung City with |an |age r|ange of 17 ye|ars |and over. The d|at|a |an|alysis technique used is multiple regression test using SPSS version 26. The results showed th|at product qu|ality h|as |a positive |and signific|ant effect on repurch|ase interest. Price perception h|as |a positive |and signific|ant effect on repurch|ase intention. Br|and im|age h|as |a positive |and signific|ant effect on repurch|ase intention. Then, product qu|ality, price perception, |and br|and im|age simult|aneously |affect repurch|ase intention.